1999
DOI: 10.1038/sj.bjp.0702864
|View full text |Cite
|
Sign up to set email alerts
|

A major role for the Rho‐associated coiled coil forming protein kinase in G‐protein‐mediated Ca2+ sensitization through inhibition of myosin phosphatase in rabbit trachea

Abstract: G protein‐mediated Ca2+ sensitization of airway smooth muscle contraction was investigated with respect to the relative importance of Rho‐associated coiled coil forming protein kinase (ROCK) and protein kinase C (PKC). We examined the effects of Y‐27632, a ROCK inhibitor, and GF 109203X, a PKC inhibitor, on guanosine 5′‐O‐(3‐thiotriphosphate) (GTPγS)‐induced contraction in α‐toxin‐ or β‐escin‐permeabilized rabbit trachea. Although pre‐treatment with Y‐27632 dose‐dependently inhibited GTPγS (10 μM)‐induced Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 42 publications
(81 reference statements)
2
83
1
1
Order By: Relevance
“…2, the contractile rate (T 1/2 ) was comparable between 8-BrcAMP-treated strips and control strips. The T 1/2 of the strips treated with a phosphatase inhibitor (such as microcystin-LR or calyculin A) is dependent on the MLCK- associated mechanisms in the presence of Ca 2ϩ (13,16). These results suggest that cAMP/PKA signaling preferentially affects MLCP-associated mechanisms of Ca 2ϩ sensitization in rabbit tracheal smooth muscle.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…2, the contractile rate (T 1/2 ) was comparable between 8-BrcAMP-treated strips and control strips. The T 1/2 of the strips treated with a phosphatase inhibitor (such as microcystin-LR or calyculin A) is dependent on the MLCK- associated mechanisms in the presence of Ca 2ϩ (13,16). These results suggest that cAMP/PKA signaling preferentially affects MLCP-associated mechanisms of Ca 2ϩ sensitization in rabbit tracheal smooth muscle.…”
Section: Discussionmentioning
confidence: 58%
“…However, precise time-course studies suggest that initiation of contraction occurred within milliseconds and that the early phase of maintenance of force occurred within several seconds (25). Furthermore, we have demonstrated that MLCK inhibition with wortmannin but not Rho-kinase inhibition with Y-27632 slowed force developments under the same experimental conditions (13). The final amplitudes were not different.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations